ANALYSIS OF KOKAND NATIONAL PATTERNS - To’laboyeva Shahlo Sobirjon qizi; Bozorboyev Nozimjon Dolimjon o’g’li; Mirxamidova Shakhzoda Mirabdullojon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
Architectural art plays an important role in the folk art of Uzbekistan. This art came with a pattern for construction materials and products in Central Asian architecture. The art of pattern and painting, which is the alphabet of applied decorative art, is one of the wonderful types of folk applied art. This article examines the architectural decorations on the roof of a building in the city of Kokand.